Recovery of Synthetic Zika Virus Based on Rio-U1 Isolate Using a Genetically Stable Two Plasmid System and cDNA Amplification - de Mello, Iasmim Silva; Fernandes, Déberli Ruiz; Furtado, Nathália Dias; dos Santos, Alexandre Araújo Cunha; dos Santos, Marta Pereira; Ribeiro, Ieda Pereira; Raphael, Lidiane Menezes Souza; Nogueira, Mônica da Silva; da Cruz, Stephanie Oliveira Diaz; Rocha, Adalgiza da Silva; Manso, Pedro Paulo de Abreu; Pelajo-Machado, Marcelo; et al. (Frontiers in Microbiology, 2021)
In 2016, the world experienced unprecedented Zika epidemic. The ZIKV emerged as major human pathogen due to its association with the impairment of perinatal development and Guillain-Barré syndrome. The occurrence of these severe cases of Zika points to the significance of studies for understanding the molecular determinants of flavivirus pathogenesis. Reverse genetics is a powerful method for studying replication and determinants of pathogenesis, virulence, and viral attenuation of flaviviruses, facilitating the design of vaccines and therapeutics. However, the main hurdle in the development of infectious clones is the instability of full-length cDNA in Escherichia coli. Here, we described the development of a genetically stable and efficient infectious clone based on the ZIKV Rio-U1 isolated in 2016 epidemic in Brazil. The employed strategy consisted of cloning the viral cDNA genome into two stable plasmid subclones and obtaining a high-quality cDNA template with increment in DNA mass for in vitro transcription by PCR amplification. The strategy for developing a ZIKV infectious cDNA clone designed in this study was successful, yielding a replicative and efficient cloned-derived virus with high similarities with its parental virus, Rio-U1 by comparison of the proliferation capacity in mammal and insect cells. The infection of AG129 immunocompromised mice caused identical mortality rates, with similar disease progression and morbidity in the animals infected with the parental and the cDNA-derived virus. Histopathological analyses of mouse brains infected with the parental and the cDNA-derived viruses revealed a similar pathogenesis degree. We observed meningoencephalitis, cellular pyknosis, and neutrophilic invasion adjacent to the choroid plexus and perivascular cuffs with the presence of neutrophils. The developed infectious clone will be a tool for genetic and functional studies in vitro and in vivo to understand viral infection and pathogenesis better.